2010
DOI: 10.1038/sj.bjc.6605563
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia as a prognostic and predictive factor in metastatic renal cell carcinoma

Abstract: BACKGROUND: Low serum sodium has recently been associated with poor survival in localised renal cell carcinoma (RCC). We now show the prognostic effect of serum sodium in patients with metastatic RCC (mRCC). METHODS: Cohort A comprised 120 consecutive patients with mRCC receiving subcutaneous, low-dose interleukin-2 and interferon-a. Hyponatremia was assessed in univariate and multivariate analyses. An independent cohort of another 120 patients with mRCC was used for validation (cohort B). RESULTS: In cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 30 publications
5
71
0
1
Order By: Relevance
“…In this same study, the authors observed that hyponatremic patients had lower survival in multivariate analysis. Furthermore, hyponatremia was associated with lack of response (by RECIST) to cytokines [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this same study, the authors observed that hyponatremic patients had lower survival in multivariate analysis. Furthermore, hyponatremia was associated with lack of response (by RECIST) to cytokines [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Serum sodium has been analyzed in mRCC patients treated with cytokines [9], and hyponatremia was found to be associated with a worse outcome. Similar observations have been made in malignancies, such as advanced hepatocellular carcinoma [10], advanced gastric cancer [11], advanced small cell lung cancer [12], and localized RCC [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hyponatremia is reported to be associated with poor survival in several carcinomas, such as hepatocellular carcinoma, 11 gastric cancer 12 and small cell lung cancer 13 . In terms of RCC, hyponatremia has been associated with poor survival in localized RCC and mRCC treated with immunotherapy 14–16 . However, there are no reports on the relationship between hyponatremia and the prognosis of mRCC treated with molecular targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for the hyponatremia may be a renal dysfunction in the exchange mechanism of sodium in the tubules. Jeppesen et al [12] reported that low values of serum sodium were significantly prognostic and predictive factors in patients with metastatic renal cell carcinoma. Although we were not able to specify the mechanism of hyponatremia in our case, the toxic effects of sorafenib include decreased papillary solute content and maximal urinary osmolality, which are major factors for increasing vasopressin secretion.…”
Section: Discussionmentioning
confidence: 99%